Implementation of Marketing Strategies to Increase Jamu Purchasing Decisions at As-Shahih Kertosono Jamu Shop - Sabrina Qutratu'ain, Naila; Samari, Samari (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research aim : The purpose of this study is to analyze how the marketing strategy carried out by the As-Shahih Jamu Shop in an effort to increase herbal purchasing decisions, using the marketing mix or 4P marketing mix, namely (Product, Price, Place, Promotion). Design/Methode/Approach : The type of research used is descriptive qualitative research. In data collection techniques using three methods, namely observation, interviews. The main data sources used in this study are from herbal medicine consumers who have been categorized as old consumers, new consumers, and young consumers as well as supporting informants from the owner of As-Shahih Herbal Shop. Research Finding : The results showed that the 4P marketing mix strategy (Product, Price, Place, Promotion) has been successfully implemented by the owner of the As-Shahih Jamu Shop, but has not yet provided significant results. As-shahih herbal products use premium raw materials that have been confirmed to have a health department, the purity of herbs without the addition of chemical drugs is a product advantage, the herbal variants available are also quite diverse. The price set by the owner is in accordance with the market price and the efficacy obtained by consumers. The location used is very strategic and easy to access by consumers. The promotion provided by the shop owner is only limited to stories from Whatsapp and Facebook, as well as consumers who inform jamu as-shahih to potential consumers through word of mouth, there are no special promotions and social media accounts made by the owner of the As-Shahih Jamu Shop. Theoretical contribution/Originality : This research is expected to contribute theoretically by expanding the understanding of the implementation of the 4P marketing mix strategy which shows product quality, market pricing, strategic location, and effective and efficient promotion can improve consumer purchasing decisions. Practitionel/Policy implication : Practical implications include the implementation of promotional policies by optimizing social media such as Instragram and Tiktok in order to attract more consumers, as well as providing shopping coupons for jamu purchases as a consumer loyalty program. In addition, registering products on online shopping applications such as Grabfood and Gojek can expand market reach. Research limitation : The main focus in this research lies on the marketing strategies used to increase herbal medicine purchasing decisions.